The Power of Information: Evidence from a Newspaper Campaign to Reduce Capture - Reinikka, Ritva; Svensson, Jakob (World Bank, Washington, D.C., 2013)
The authors exploit an unusual policy experiment to evaluate the effects of increased public access to information as a tool to reduce capture and corruption of public funds. In the late 1990s, the Ugandan government initiated a newspaper campaign to boost schools' and parents' ability to monitor local officials' handling of a large school-grant program. The results were striking: capture was reduced from 80 percent in 1995 to less than 20 percent in 2001. The authors use distance to the nearest newspaper outlet as an instrument for exposure to the campaign. Proximity to a newspaper outlet is positively correlated with the head teachers' knowledge about rules governing the grant program and the timing of releases of funds from the center, but uncorrelated with test scores of general ability. A strong (reduced-form) relationship exists between proximity to a newspaper outlet and reduction in capture of school funds since the newspaper campaign started. This pattern contrasts sharply with the outcomes in the five-year period prior to the campaign. Instrumenting for head teachers' knowledge about the grant program, the authors find that public access to information is a powerful deterrent to capture at the local level.